1976
DOI: 10.1021/i260060a015
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Gas Mixtures Containing Common Polar and Nonpolar Components

Abstract: The vessel inside and coil outside film heat transfer coefficients of water and dilute aqueous polymer solutions of sodium carboxymethyl cellulose (SCMC) and sodium alginate (SA) have been studied in a turbine-agitated vessel for standard and nonstandard vessel configurations with agitator diameter, depth of agitation, helix diameter, and coiled tube outside diameter as parameters. The jacket-and coil-side heat transfer results are correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…[8,17,18]. In general, these equations showed better or comparable performance to the PR and SRK equations in calculating fluid phase equilibrium properties of simple mixtures.…”
Section: The Repulsive Termmentioning
confidence: 81%
“…[8,17,18]. In general, these equations showed better or comparable performance to the PR and SRK equations in calculating fluid phase equilibrium properties of simple mixtures.…”
Section: The Repulsive Termmentioning
confidence: 81%
“…In addition, for the vapour-liquid equilibrium the Maxwell rule is applied. For each experimental point (T=constans) a system of three equations with three unknown EOS parameters was solved: (9) where…”
Section: The Modification Of the Nakamura -Breedveld-prausnitz Equatimentioning
confidence: 99%
“…This is a perturbedhard-sphere equation of state. It was given for gases and their mixtures containing highly polar molecules (such as water, ammonia or sulfur dioxide) and the non-polar or slightly polar molecules (such as hydrogen, argon, nitrogen, carbon monoxide, methane, ethane, ethylene, propane, propylene, hydrogen sulfide or carbon dioxide) 9 . In order to describe the supercritical fluids better, the NBP EOS was successfully modified by Kozio³ 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper6), the perturbed-hard-sphere equation of state proposed by Nakamura et al 7) has been found to be successful to represent both the p-v-T relations and the second and third virial coefficients for water vapor. In the present study, the equation of state is applied to correlate the solubility of water in several compressed nonpolar gases.…”
Section: Introductionmentioning
confidence: 99%